Knowledge, application and assessment of the information technology and communication (ICT) 2.0 students and teachers from the Faculty of Dentistry of the University of San Marcos: undergraduate and graduate - Evaristo Chiyong, Teresa (2016)
Objective: This research aims to analyze the knowledge, application and assessment about the Information and Communication Technology (ICT) of Web 2.0 in education. The Web 2.0 consider the use of applications and websites willing to use the collective intelligence through social software to facilitate the learning processes. Materials and method: An observational, descriptive, cross-sectional study was conducted in a simple random pro-bability sample of 173 students and 109 undergraduate and graduate respectively and 54 teachers. The questionnaire was validated by expert judgment obtaining a coefficient Aiken V equal to 1, and Cronbach alpha reliability of 0.75. Results: The results showed that the three groups recognized communication tools as a mechanism to share information, improve teacher relationship and develop collaborative work with percentages above 80 %. The assessment of the use of them is rated as good in 58.9 %, 66.1 % and 72 % of undergraduate students, graduate students and teachers respectively. The use of these tools is higher in undergraduate students 92.6 % followed by graduate 82.6 % and teachers 69.8 %. The knowledge of the various tools of generation and publication of content is present in the three groups. The recovery and finding information tool most used by teachers and graduate students were specialized databases. Conclusions: There is a positive trend to use these tools within the educational field.